Regulation of memory antibody levels: the role of persisting antigen versus plasma cell life span. - Gatto, D; Martin, S; Bessa, J; Pellicioli, E; Saudan, P; Hinton, H; Bachmann, M (2007)
Protective Ab levels can be maintained for years upon infection or vaccination. In this study, we studied the duration of Ab responses as a function of the life span of plasma cells and tested the role of persisting Ag in maintaining B cell memory. Our analysis of B cell responses induced in mice immunized with virus-like particles demonstrates the following: 1) Ab titers are long-lived, but decline continuously with a t(1/2) of approximately 80 days, which corresponds to the life span of plasma cells; 2) the germinal center (GC) reaction, which lasts for up to 100 days, is dependent on Ag associated with follicular dendritic cells; and 3) early GCs produce massive numbers of plasma and memory B cell precursors, whereas the late Ag-dependent GCs are dispensable for the maintenance of Ab levels and B cell memory.